(untitled) (Estudos em Design, 2019)
This paper argues that the space in a website storyworld becomes a meaningful dimension when the background and the elements form a spatial continuum that will lead to space-medium remediation. The close reading method was applied to investigate how space was designed as a meaningful dimension on the Le-Mugs hip canteen website. The findings indicate that the design of the space of the medium created a meaningful dimension because parallax scrolling reinforces depth on transitioning from one state to another and the pictures sequencing remediates film-editing metaphor. In addition, the one-page format remediates papyrus scroll and privileges sequencing that facilitate storytelling. The user trajectory varies the point of view from top to bottom view, which highlights hypermediation. Finally, the interaction between the user and space is transformed into interactions between the background and the objects, and our experience of this virtual space becomes structured as a visit where the limits of space are explicit within the space itself. This remediation of the screen reinforces a core message: for this hip canteen, the space is as important as the food.